Combined Energy Supply System for Meat Processing Plants - Sit M.; Sit B. (Problems of the Regional Energetics)
The purpose of this study is the development of technological schemes of energy production for this industry in terms of energy efficiency. Technical solution that can reduce cost of the final production of meat production plant has been presented. The main idea of the tehnical solution is the use of turboexpander, which must be installed on gas reduction station near meat processing plant in the packet with the „air-water” gas – driven heat pump, which gas cooler serves as gas heating unit for the first stage of turboexpander. The thermal exit of gas engine serves as gas heating unit for the second stage of turboexpander and as heat energy generator for the plant and source of the heat for one of the evaporators of heat pump, as well. The second evaporator of heat pump is connected with the cold consuming equipment of the plant. The electric energy, which is produced by gas engine is consumed by heat pump compressor and electric equipment of the plant. Electric energy, which is produced by turbo expander is transmitted to the electric grid. The proposed technical solution can be used to reduce natural gas consumption on meat processing plants and the cost of production of electricity, heat and cold.